Plan de marketing para el almacén “tres hermanos” cantón Buena Fe, año 2015 - Murillo Loor, Wendy Yuliana (2016)
The three brothers store is a company that sells appliances in the city of Buena Fe, its main objective is to meet the requirements of the target market. This research project has as main objective to develop a marketing plan, which allows the storage appliance to have a detailed picture of the target market in which it operates, through study of the needs of customers and increasing sales and acceptance of products and services and strengthen its image to achieve more forces penetrate those markets. The study contains an analysis of the current status of warehouse appliances "Three Brothers", where it is found that does not have a marketing plan that allows you to achieve a better positioning in the market, there is strong competition forcing the store to increase stop your product, in order to satisfy and retain current and potential customers. SWOT, product, price, promotion and place that facilitate the increased supply store products in the market and achieve a better positioning in the competition: which marketing strategies are determined. The budget was established as a tool to promote planning in different areas of the company to decide which actions to take and to allow the plan to implement structured marketing strategies to be implemented and where considered all factors of the company and the environment required for efficient decision-making needed to seize the opportunities and minimize the threats it faces in a competitive as exists in the city of Buena Fe market, whereas the marketing is critical for better positioning of the store and thus avoid to stagnate, whereas the general budget as we 17,105.00.